A new strategy using entomopathogenic fungi for the control of tree borer insects. Issue 7 (29th July 2022) - Shin, Tae Young; Lee, Mi Rong; Kim, Jong‐Cheol; Nai, Yu‐Shin; Kim, Jae Su
Abstract: In order to establish a strategy for controlling pests living in trees and causing damage, injected entomopathogenic fungal conidia suspension of Beauveria bassiana into a four‐year‐old Canary Island date palm, Phoenix canariensis . As a result, B. bassiana Bb‐egfp#3 expressing green fluorescent protein was dispersed from the injection site to the top and bottom of the tree. To evaluate the insecticidal activity of the Bb‐egfp#3 injected into the tree, we released mealworm larvae ( Tenebrio molitor ) on the ground palm tree sample that was injected with the conidia suspension. As a result, mycosis caused by the injected Bb‐egfp#3 in the trees was generated in all cadavers. This study suggests the possibility of establishing a new control strategy against tree pests by injecting an entomopathogenic fungal conidia suspension into trees.